The Importance of Learning the Dutch Language and Culture for the Croatian Society - Pancirov Cornelisse, Željana (Array, 2010)
In today's multilingual society it is very important to speak as many languages as possible. In Croatian society, the Dutch language is not always the first choice. Why would anyone learn Dutch? And why in Croatia? What can one do with a degree in Dutch Language and Cultural Studies? Such questions are often asked to the students and lecturers of the Dutch Division at the Faculty of Humanities and Social Sciences, University of Zagreb. The Division opened its door in the academic year 2008-2009. There is a growing need for the Dutch language and cultural expertise in Croatia, even though many find this language too exotic, frequently accompanied by prejudice. The opening of the new Division proved that the interest is not to be passed as something unimportant, but on the contrary, it is a prosperous language with a rich culture and a great future. What is the need and the motivation of Croatian students to study the Dutch language with its cultural aspects? What should be considered when positioning the importance of the Dutch language in Croatian society? The answers to these questions can help to improve the quality of the studying process and emphasize the problems that need to be solved in the future.